Integral methods of measuring the population life quality in local communities of the region - Getmantsev Konstantin V.; Myasnikova Tatiana A.; Rodin Alexander V.; Silchenko Kristina V. (E3S Web of Conferences, 2023)
The presented article discusses the method of constructing an integral indicator of measuring the life quality. An important problem in assessing the life quality of the population is the complex nature of this concept, covering a variety of quantitative and qualitative characteristics. Currently, in the absence of the possibility of conducting scientific research on a wide range of indicators at once, selective methods are used using a small number of indicators for assessing the life quality of the population. The authors propose to use a three-stage procedure for constructing an integral indicator based on the calculation of primary indicators, the procedure for their normalization and the construction of the final integral indicator for assessing the life quality of the population. Such a technique opens up wide opportunities for further scientific regional research, since it allows conducting research in the context of local territories of the region, as well as on the entire region scale.